IS THERE A RELATIONSHIP BETWEEN SELF-EFFICACY AND STUDENT’S BIOLOGY LEARNING COMPETENCE? - Maharani Kurnia Sari; Yosi Laila Rahmi; Ilmi Zajuli Ichsan (Universitas Negeri Padang, 2021)
Education is a conscious and planned effort to develop the potential of students through learning activities. The achievement of learning activities can be seen from the learning outcomes obtained by students. This learning outcome is related to the competence of students. There are several factors that influence learning outcomes, one of which is self-efficacy. Self-efficacy is needed to see students' confidence in learning activities such as biology. This study aims to determine the relationship between self-efficacy and the biology learning competence of students. The type of research is descriptive with the type of correlation. The population of this research is students at Senior High School Pertiwi 2 Padang, totaling 70 people with a sampling technique that is saturation sampling. The data of this study are self-efficacy obtained through questionnaires and data on the biology learning competence of students obtained from the odd semester final exam. Data analysis in this study was carried out by statistical test, namely Pearson Product Moment. The results of the statistical test showed that there was a relationship between self-efficacy and the biology learning competence of students. The correlation coefficient values obtained indicate a low relationship between self-efficacy and the biology learning competence of.